Mendelian randomization analysis of causal relationship between celiac disease and autoimmune thyroid disease - YAN Junhao; GUO Xiaolei; LUO Zhaofeng; TANG Jian; WANG Zheng (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2025)
Objective·To investigate the bidirectional causal relationships between celiac disease (CeD) and Hashimoto thyroiditis (HT) as well as Graves disease (GD), using a two-sample Mendelian randomization (MR) approach.Methods·Single nucleotide polymorphisms (SNPs) related to CeD, HT and GD were extracted from publicly available Genome-Wide Association Studies (GWAS) databases and used as instrumental variables. The inverse-variance weighted (IVW) method served as the primary analytical approach, supplemented by MR-Egger, weighted median (WME) and weighted mode (WMO) methods, to evaluate the causal associations between CeD and both HT and GD. Replication analyses using alternative GWAS datasets were conducted to validate the robustness of the results. Heterogeneity was assessed using Cochran's Q test, and pleiotropy was evaluated via MR-Egger intercept test. Leave-one-out analyses were performed to assess the impact of individual SNPs on the results.Results·The IVW analysis results indicated that genetically predicted CeD significantly increased the risk of HT [discovery group: OR=1.186 (95%CI 1.114‒1.262), P<0.001; replication group: OR=1.218 (95%CI 1.090‒1.361), P<0.001] and GD [discovery group: OR=1.214 (95%CI 1.155‒1.276), P<0.001; replication group: OR=1.273 (95%CI 1.161‒1.396), P<0.001]. However, reverse MR analyses did not provide evidence for a causal relationship between HT and CeD, while genetically predicted GD significantly increased the risk of CeD [discovery group: OR=1.259 (95%CI 1.006‒1.576), P=0.044; replication group: OR=1.387 (95%CI 1.233‒1.560), P<0.001]. Sensitivity analyses suggested that the results were not influenced by horizontal pleiotropy.Conclusion·CeD may be causally associated with a higher risk of HT and GD, while GD may increase the risk of developing CeD. HT does not appear to have an impact on CeD.